Wind energy and landscape : proceedings of the International Workshop on Wind Energy and Landscape, WEL, Genova, Italy, 26-27 June 1997 /: proceedings of the International Workshop on Wind Energy and Landscape, WEL, Genova, Italy, 26-27 June 1997. (2020) - Unknown
No abstract available